Beneficial effects of a mouthwash containing an antiviral phthalocyanine derivative on the length of hospital stay for COVID-19: randomised trial - Paulo Sérgio da Silva Santos; Bernardo da Fonseca Orcina; Rafael Rahal Guaragna Machado; Fabiano Vieira Vilhena; Lucas Marques da Costa Alves; Mariana Schutzer Ragghianti Zangrando; Rodrigo Cardoso de Oliveira; Mariana Quirino Silveira Soares; Andréa Name Colado Simão; Emilene Cristine Izu Nakamura Pietro; Juliana Pescinelli Garcia Kuroda; Ivanilda Aparecida de Almeida Benjamim; et al. (Scientific Reports, 2021)
Abstract The risk of contamination and dissemination by SARS-CoV-2 has a strong link with nasal, oral and pharyngeal cavities. Recently, our research group observed the promising performance of an anionic phthalocyanine derivative (APD) used in a mouthwash protocol without photoexcitation; this protocol improved the general clinical condition of patients infected with SARS-CoV-2. The present two-arm study evaluated in vitro the antiviral activity and cytotoxicity of APD. Additionally, a triple-blind randomized controlled trial was conducted with 41 hospitalized patients who tested positive for COVID-19. All the included patients received World Health Organization standard care hospital treatment (non-intensive care) plus active mouthwash (experimental group AM/n = 20) or nonactive mouthwash (control group NAM/n = 21). The adjunct mouthwash intervention protocol used in both groups consisted one-minute gargling/rinsing / 5 times/day until hospital discharge. Groups were compared considering age, number of comorbidities, duration of symptoms prior admission and length of hospital stay (LOS). The associations between group and sex, age range, presence of comorbidities, admission to Intensive care unit (ICU) and death were also evaluated. The in vitro evaluation demonstrated that APD compound was highly effective for reduction of SARS-CoV-2 viral load in the 1.0 mg/mL (99.96%) to 0.125 mg/mL (92.65%) range without causing cytotoxicity. Regarding the clinical trial, the median LOS of the AM group was significantly shortened (4 days) compared with that of the NAM group (7 days) (p = 0.0314). Additionally, gargling/rinsing with APD was very helpful in reducing the severity of symptoms (no ICU care was needed) compared to not gargling/rinsing with APD (28.6% of the patients in the NAM group needed ICU care, and 50% of this ICU subgroup passed way, p = 0.0207). This study indicated that the mechanical action of the protocol involving mouthwash containing a compound with antiviral effects against SARS-CoV-2 may reduce the symptoms of the patients and the spread of infection. The use of APD in a mouthwash as an adjuvant the hospital COVID-19 treatment presented no contraindication and reduced the hospital stay period. Trial registration: The clinical study was registered at REBEC—Brazilian Clinical Trial Register (RBR-58ftdj).